Release of Microplastic Fibers from Polyester Knit Fleece during Abrasion, Washing, and Drying - Novotna, Jana; Tunak, Maros; Militky, Jiri; Kremenakova, Dana; Wiener, Jakub; Novakova, Jitka; Sevcu, Alena (ACS omega, 2025)
Today, microplastics are found in soil, air, and all water sources, including rivers, groundwater, and treated drinking water, with the majority originating from wastewater produced during the washing process. The aim of this study is to determine how standard washing, drying, and wearing simulated by mechanical abrasion of 100% polyester multifilament fleece knitted fabrics contribute to the release and formation of microplastics and fibrous fragments by determining changes in their total weight, thickness, dimensions, and relative surface area. In addition, a new textile surface evaluation methodology was developed to assess the cover area (cover ratio) of released microplastic fibers trapped on the treated fabric surface. The standard and new methods confirmed that the amount of microplastic fibers released from the fleece fabric increased continuously until the third to fifth washing cycle, after which the released amount was nearly constant. Furthermore, a large proportion of the released microplastic fibers was shown to have originated as residue from the manufacturing process. We recommend that (i) washing machines should include a 25 × 30 μm mesh fabric filter to reduce the number of microplastic fibers released down the drain, (ii) flat textiles should be prewashed in the factory, thereby effectively capturing the more significant part of fibers released during the first washing cycle, (iii) the construction and properties of fleece fabrics should be improved to meet environmental requirements, and (iv) the newly developed method for analyzing the cover area of loose fibers on fabric surfaces can be more widely used for quality control.